Strategi Pembelajaran Daring Luring Dalam Upaya Mengatasi Kesulitan Belajar Siswa Pada Masa Pandemi Covid-19 Di Sdn Kramat 3 Kota Magelang - Rianto, Defi Nadata Putri (Prosiding University Research Colloquium, 2021)
The existence of cases of learning difficulties experienced by students during the Covid-19 pandemic made student less understand the subject matter presented by the teacher. This study aims to determine the learning strategy of daring to captivate in an effort to overcome student learning difficulties during the COVID-19 pandemic at SDN Kramat 3 Magelang City. This research applies a qualitative case study. Data were collected using a questionnaire from interviews. The sample used in this study was a 4th grade teacher at SDN Kramat 3 Magelang City. The results of this study indicate that learning courage affects the learning difficulties of grade 4 students at SDN Kramat 3 Magelang City. Keywords: Strategy, Offline Learning.